A five—year follow—up study on the pathological changes of gastric mucosa after H.pylori eradication - 周丽雅 沈祖尧 林三仁 金珠 丁士刚 黄雪彪 夏志伟 郭慧兰 刘建军 (Chinese medical journal, 2003)
Objectives To investigate the relationship between H.pylori infection,gastric cancer and other gastric diseases through the changes in gastric mucosa and the status of different gastric diseases within 5 years after H.pylori eradication in H.pylori-positive subjects in a high incldence region of gastric cancer. Methods One thousand and six adults were selected from the general population in Yantai,Shandong province,a high Incidence region for gastric cancer in China.Gastroscopy and Campylobacter-like organism(CLO)testing were performed on all subjects,Biopsy samples from the gastric antrum and body were obtained for histology and assessment of H.pylori infection.All H.pylori-positive subjects were then randomly divided into two groups:treatment group receiving Omeprazole Amoxicillin Clarythromycin(OAC) triple therapy and placebo as controls.These subjects were endoscopically followed up in the second and fifth year.We compared the endosopic appearance and histology of the biopsy specimens from the same site obtained at the first and last visits.Results All 552H.pylori-positive subjects were randomly and evenly divided into treatrment group or control group.During the five-year follow-up,the numbers of patients who continued to be negative or positive for H.pylori were 161 and 198,respectively.Statistical analysis revealed that:①At the initial visit,there were no significant differences in the severity and activity of inflammation,atrophy and intestinal metaplasia between the biopsy specimens from the antrum and body resopectively in both groups. ②The severity and activity of inflammation in both the antrum and body were markedly reduced after H.pylori eradication(P=0.000).③Within five years after H.pylori eradication,intestinal metaplasia in the antrum either regressed or had no progression,while the proportion of intestinal metaplasia in the H.pylori-positive group increased significantly(P=0.032).④After H.pylori eradication,the atrophy in both the antrum and body had no significant regression.The P value was 0.223 and 0.402,respectively.Conclusions H.pylori eradication results in remarkable reduction in the severity and activity of chronic gastritis,marked resolution of intestinal metaplasia in the antrum.On the other hand.continuous H.pylori infection leads to progressive aggravation of atrophy and intestinal metaplasia.